A Parametric Study on the Immunomodulatory Effects of Electroacupuncture in DNP-KLH Immunized Mice. (14th February 2011) - Kim, Sun Kwang; Lee, Youngseop; Cho, Hyunjoo; Koo, Sungtae; Choi, Sun Mi; Shin, Min-Kyu; Hong, Moo-Chang; Min, Byung-Il; Bae, Hyunsu
Abstract : This study was conducted to compare the effects of low frequency electroacupuncture (EA) and high frequency EA at acupoint ST36 on the production of IgE and Th1/Th2 cytokines in BALB/c mice that had been immunized with 2, 4-dinitrophenylated keyhole limpet protein (DNP-KLH), as well as to investigate the difference in the immunomodulatory effects exerted by EA stimulations at acupoint ST36 and at a non-acupoint (tail). Female BALB/c mice were divided into seven groups: normal (no treatments), IM (immunization only), ST36-PA (IM + plain acupuncture at ST36), ST36-LEA (IM + low frequency (1 Hz) EA at ST36), ST36-HEA (IM + high frequency (120 Hz) EA at ST36), NA-LEA (IM + low frequency (1 Hz) EA at non-acupoint) and NA-HEA (IM + high frequency (120 Hz) EA at non-acupoint). EA stimulation was performed daily for two weeks, and total IgE, DNP-KLH specific IgE, IL-4 and IFN- γ levels were measured at the end of the experiment. The results of this study showed that the IgE and IL-4 levels were significantly suppressed in the ST36-LEA and ST36-HEA groups, but not in the NA-LEA and NA-HEA groups. However, there was little difference in the immunomodulatory effects observed in the ST36-LEA and ST36-HEA groups. Taken together, these results suggest that EA stimulation-induced immunomodulation is not frequency dependent, but that it is acupoint specific.